Adolescent Baseball Pitchers With Ulnar Collateral Ligament Tears Exhibit a High Proportion of Partial Tears. Issue 8 (July 2022) - Goodrich, Eric; Cox, Benjamin; Plummer, Hillary A.; Cohen, Achraf; Andrews, James R.; Saper, Michael
Background: Ulnar collateral ligament (UCL) tears in the throwing elbow are classified according to grade and location using magnetic resonance arthrography (MRA). However, the frequency of each tear type and the association to age, competition level, and radiographic findings in adolescent baseball pitchers are unknown. Purposes: The primary purpose of this study was to use MRA to characterize the severity, location, and UCL tear type in adolescent pitchers. The second aim was to describe the relationship between the UCL tear type and age, competition level, and plain radiographic findings. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Records of adolescent pitchers with a UCL tear treated by the senior author between 2007 and 2016 were retrospectively reviewed. MRA scans were reviewed and tears were classified according to the Joyner-Andrews classification. Low-grade partial tears are classified as type I, high-grade partial tears as type II, complete full-thickness tears as type III, and tear pathology in >1 region in the UCL as type IV. Each type of tear also has a location designated at the midsubstance, ulna (U), or humerus (H). Patient characteristics, competition level, and associated plain radiographic abnormalities were recorded. Univariate analyses were performed to examine the relationships between tear types and age, competition level, and plain radiographic findings. Results: A total of 200 adolescent pitchers (mean ± SD age, 17.2 ± 1.5 years) with MRA scans were reviewed. Type II-H (n = 62), type II-U (n = 51), and type III-U (n = 28) were the most common tear types observed. Type II tears comprised 64.5% of adolescent UCL tears, with type II-H being the most common. Plain radiographs were abnormal in 32% of patients, with calcifications (10.5%) and olecranon osteophytes (12.5%) being the most common findings. There were no significant relationships between tear type and age ( P = .25), competition level ( P = .23), or radiographic abnormalities ( P = .75). Conclusion: Humeral-sided high-grade partial tears were the most common tear type in adolescent pitchers. There was no relationship between UCL tear type and age competition level, and plain radiographic abnormalities.